ANALISIS TELUR CACING SOIL TRANSMITTED HELMINTH (STH) PADA PETANI SAYUR DI KUBANG RAYA KOTA PEKANBARU - Berliana N.R.S. Aritonang (Jurnal Sains dan Teknologi Laboratorium Medik, 2022)
Worm infection caused by the Soil Transmitted Helminth (STH) are still a health problem for the community, especially for vegetable farmers whose work is directly related to land. Worm whose development requires soil to be an infective form, namely the Soil Transmitted Helminth (STH). The types of Soil Transmitted Helminth (STH) worm are Ascaris lumbricoides, Trichuris trichiura, Ancylostoma duodenale and Necator americanus. The purpose of this study was to identify the STH eggs in stools of vegetable farmers at Kubang Raya Pekanbaru. The sampling technique used was quota sampling. The examination method used were with mount direct and sedimentation method. Based on microscopic examination of 6 faecal samples with the direct method, STH eggs were not found in all sample. Meanwhile in the observation with sedimentation method, 1 of 6 samples was found to be positive for hookworm eggs (sample GP).